A prospective study of colonoscopic examination at al-kindy teaching hospital - Hassan, Riyadh Mohammad (AL-Kindy College Medical Journal, 2010)
Background: Fiber-optic endoscopy is an importantinvestigation of the large intestine, whether or not theradiologist (barium enema) has discovered a lesion inthe bowel. Colonoscopy affords a unique opportunityto direct visualization of entire colonic mucosa. Atthe same time, the physician can obtain biopsy specimens, remove polyps, and decompress volvuli.Most experienced endoscopists and well preparedpatients can reach the cecum in over 90% of patients.If colonoscopy is properly performed, it has a lowrisk of complications, such as perforation and bleeding.Methods: A total of 70 consecutive patients admittedto Endoscopy department at Al-Kindy Teaching hospital from September- 2008 to July-2009. Bowelpreparation was achieved with Polyethylene glycollavage solution and 165 cm Pentax colonoscopeEC_3385FK 4.2 was used in all cases. All patientswere not sedated or given any other medicationResults:Seventy colonoscopies were performed inthis study. Forty of them were male and the rest werefemale. The mean age was 42 years ranging from 4years to 85 years. The most common indication forcolonoscopy was rectal bleeding (44%) Polyethyleneglycol lavage solution was used in all patients forbowel preparation. All patients did not receive premedications. Complete colonoscopy examination wasdone in (12.8%) of patients, the most common causeof incomplete examination was poor bowel preparation (50%). No complications were reported.Conclusions: Rectal bleeding was the most commonindication for colonoscopy. Poor bowel preparationwas the main cause of incomplete colonoscopy.